2018
DOI: 10.7883/yoken.jjid.2017.183
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification of <i>Neisseria cinerea</i> as <i>Neisseria meningitidis</i> by Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS)

Abstract: Communicated by Makoto OhnishiMatrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) is used as a rapid and accurate microbial diagnostic method for species identification of pathogens. At our hospital, we use MALDI-TOF MS for rapid identification of microorganisms from pathogen-positive blood cultures. In this article, we report a case where Neisseria meningitidis was confirmed via blood culture using MALDI-TOF MS, but the microbe was ultimately confirmed to be Neisseria c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…Our findings correlate with the data presented by Hong et al in which two isolates of Neisseria polysaccharaea, two Neisseria cinerea and one Neisseria bergeri were misidentified as N. meningitidis using Bruker MALDI Biotyper [2]. In a case reported from Japan, a blood isolate of N. cinerea was named as N. meningitidis by MALDI-TOF MS [6]. Also, Cunningham et al reports five isolates of N. polysaccharea with an identification problem as meningococci [7].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings correlate with the data presented by Hong et al in which two isolates of Neisseria polysaccharaea, two Neisseria cinerea and one Neisseria bergeri were misidentified as N. meningitidis using Bruker MALDI Biotyper [2]. In a case reported from Japan, a blood isolate of N. cinerea was named as N. meningitidis by MALDI-TOF MS [6]. Also, Cunningham et al reports five isolates of N. polysaccharea with an identification problem as meningococci [7].…”
Section: Discussionsupporting
confidence: 90%
“…However, other studies suspected that the number of reference spectra in the MALDI-TOF database was insufficient, resulting in poor discriminatory power for closely related non-pathogenic Neisseria spp. [ 17 , 18 ]. To resolve this issue, some studies suggested to group N. macacae and N. mucosa isolates into the N. mucosa category and N. flavescens and N. perflava into one category with N. subflava [ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although both diplococci, N. cinerea can be differentiated from N. gonorrhoeae due to its sensitivity to colistin and its ability to proliferate on Mueller-Hinton agar [8] . The widespread implementation of matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has improved the identification of Neisseria species but remains imperfect [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%